PAC-Mediated AKI Protection Is Critically Mediated but Does Not Exclusively Depend on Cell-Derived Microvesicles. (10th March 2021) - Dihazi, H.; Schwarze, K.; Patschan, S.; Müller, G. A.; Ritter, O.; Zeisberg, M.; Patschan, D.
Abstract : Introduction . Acute kidney injury (AKI) significantly worsens the prognosis of hospitalized patients. In recent years, cell-based strategies have been established as a reliable option for improving AKI outcomes in experimental AKI. Our previous studies focused on the so-called proangiogenic cells (PACs). Mechanisms that contribute to PAC-mediated AKI protection include production/secretion of extracellular vesicles (MV, microvesicles). In addition, the cells most likely act by paracrinic processes (secretome). The current study evaluated whether AKI may be preventable by the administration of either PAC-derived MV and/or the secretome alone. Methods . AKI was induced in male C57/Bl6N mice (8–12 weeks) by bilateral renal ischemia (IRI-40 minutes). Syngeneic murine PACs were stimulated with either melatonin, angiopoietin-1 or -2, or with bone morphogenetic protein-5 (BMP-5) for one hour, respectively. PAC-derived MV and the vesicle-depleted supernatant were subsequently collected and i.v.-injected after ischemia. Mice were analyzed 48 hours later. Results . IRI induced significant kidney excretory dysfunction as reflected by higher serum cystatin C levels. The only measure that improved AKI was the injection of MV, collected from native PACs. The following conditions worsened after ischemic renal function even further: MV + Ang-1, MV + BMP-5, MV + melatonin, and MV + secretome + Ang-1. Conclusion . Together, our data show that PAC-mediated AKI protection substantially depends on the availability of cell-derived MV. However, since previous data showed improved AKI-protection by PACs after cell preconditioning with certain mediators (Ang-1 and -2, melatonin, BMP-5), mechanisms other than exclusively vesicle-dependent mechanisms must be involved in PAC-mediated AKI protection.